Gender Performance Gaps: Quasi-Experimental Evidence on the Role of Gender Differences in Sleep Cycles - Lester Lusher; Vasil Yasenov (Institute for the Study of Labor (IZA), 2016)
Sleep studies suggest that girls go to sleep earlier, are more active in the morning, and cope with sleep deprivation better than boys. We provide the first causal evidence on how gender differences in sleep cycles can help explain the gender performance gap. We exploit over 240,000 assignment-level grades from a quasi-experiment with a community of middle and high schools where students' schedules alternated between morning and afternoon start times each month. Relative to girls, we find that boys' achievement benefits from a later start time. For classes taught at the beginning of the school day, our estimates explain up to 16% of the gender performance gap.
Keywords: H52; I20; I21; 330; gender performance gap; gender difference in sleep cycles; school start time